Thermal-Driven Phase Separation of Double-Cable Polymers Enables Efficient Single-Component Organic Solar Cells - Feng, Guitao; Li, Junyu; He, Yakun; Zheng, Wenyu; Wang, Jing; Li, Cheng; Tang, Zheng; Osvet, Andres; Li, Ning; Brabec, Christoph; Yi, Yuanping; Yan, He; et al. (Joule, 2019)
Conventional organic solar cells (OSCs) need two components that function as donor and acceptor, respectively. Although there has been wishful thinking about constructing OSCs based on a single component, it is generally believed to be highly challenging to achieve efficient single-component OSCs (SCOSCs). In this work, we design a new double-cable conjugated polymer containing a strongly crystalline backbone as donor and aromatic side units as acceptor. With a high annealing temperature (230°C), both the backbones and perylene bisimide side units could self-organize into ordered nanostructures. This enables efficient charge transport and low charge recombination, resulting in a record efficiency of 6.3% in SCOSCs. The cells also exhibit excellent stability, with >90% efficiency retention over 300 h of continuous one-sun illumination. These results suggest that the concept of SCOSCs is highly promising, especially to overcome the limitations of conventional OSCs toward industrial application.
CRIS-Team Scopus Importer:2019-07-19
Keywords: conjugated polymers; double cable; nanophase separation; single-component organic solar cells; thermal driven